Revestimentos superficiais alternativos para aumento da vida útil de coquilhas de aço H13 utilizadas na fundição da liga AlSi12Cu4Ni2Mg - Bandeira Neto, Guilherme (2020)
This work was evaluated using options for protective coating which improved the hot working H13 steel mold availability in casting manufacturing of AlSi12Cu4Ni2Mg alloy. To reach this goal, the coating must be resistant to wear and to an aluminum soldering process. This takes place through aluminum diffusion from a solidified aluminum alloy in the direction of H13 steel matrix. Process cycle is a sequence of pouring melted aluminum into the mold, followed by solidification time, extraction of the finished part and the closing of the mold. In test performances, a tile of the mold, the pin, was chosen as a specimen because it has constant contact with a cast aluminum alloy, supporting additional efforts like extraction under solidified material. The tested coatings were nitrocarburized, duplex (plasma nitriding process, multilayered based-CrAlN/CrTiN coating applied by cathodic arc) and boronized. The coated pins were assembled in a same permanent mold to become susceptible to the same productive variables as in the GDC (gravity die casting) process. To understand the evaluation of the surface degradation, one specimen was segregated for each coating in different conditions, comprising of one condition with pins which did not have worked, a second condition of pins which have worked 40,000 cycles and a third condition with a maximum lifespan of nitrocarburized and duplex coating. The specimens were characterized by Vickers microhardness, optical microscopy (OM), X-ray diffraction (XRD), Scanning electron Microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and back-scattered electrons (BSE). As a conclusion, the Duplex based-CrAlN/CrTiN coating deposition by the cathodic arc in AISI H13 nitrided steel increased the mold working life within a 24% minimum, compared to the actual standard coating nitrocarburized coating. Boronized coating had an acceptable performance but to increase working life, it is necessary to adjust their production process.